Preparation of scaffolds of amorphous calcium phosphate and bacterial cellulose for use in tissue regeneration by freeze-drying process - Tiomnova, Olinka Tiomno; Coelho, Fernanda [UNESP]; Pellizaro, Thales A. Garcia [UNESP]; Chanfrau, Jorge Enrique Rodriguez [UNESP]; Capote, Ticiana Sidorenko de Oliveira [UNESP]; Basmaji, Pierre; Pantoja, Yaymarilis Veranes; Guastaldi, Antonio Carlos [UNESP] (AMG Transcend Association, 2021)
The elaboration of scaffolds for use in tissue regeneration processes plays an important role in the area of biomaterials. Natural and synthetic polymers, together with calcium phosphates, form suitable compounds for these studies because their combinations favor the union of the properties of both materials, such as their biocompatibility, biofunctionality, shape, porosity, and mechanical properties. The objective of this work was to develop a scaffold of amorphous calcium phosphate and bacterial cellulose, applying a freeze-drying process. The results demonstrated the feasibility of scaffolds elaboration applying the freeze-drying methodology. The formulation that presented the best results was the one that contained amorphous calcium phosphate (50%), bacterial cellulose gel (20%), and sodium alginate (30%). Cytotoxicity studies showed that the studied formulation did not present cytotoxicity, promoting cell viability.
Keywords: Biomaterials; Calcium phosphates; Cytotoxicity study; Freeze-drying; Scaffolds